Installation of Clean Water Piping for Resident on Jl. Arjuna, RW 08 and 09, East Labuh Baru, Pekanbaru - Zaini, Abdul Kudus; Kumalasari, Cyintia; Muttaqin, Muhammad Zainal (PT. Riset Press International, 2024)
Water is a crucial resource for sustaining life; however, access to it through the Regional Drinking Water Company (Indonesian: Perusahaan Daerah Air Minum [PDAM]) remains limited in certain communities. As a result, residents frequently depend on groundwater sourced through independent pumping by households, places of worship, public facilities, private and government offices, and others. An assessment of the buildings on Jl. Arjuna RW 08 and 09, East Labuh Baru District, Pekanbaru, indicates a significant lack of adequate clean water installation systems, highlighting a need for targeted community service efforts. This initiative aims to rectify these deficiencies by drilling wells to establish reliable sources of clean water and installing a comprehensive clean water piping system to ensure effective distribution from the source to the end users, thus aligning with Indonesian National Standards (SNI). The project involves faculty members as part of their commitment to the tri-dharma of higher education, offering both a practical learning opportunity for students and a valuable service to the community.